Emotion Regulation in Achievement Situations: An Integrated Model. Issue 2 (3rd April 2019) - Harley, Jason M.; Pekrun, Reinhard; Taxer, Jamie L.; Gross, James J.
Abstract : Achievement emotions are critical because of their impact on success and failure in important domains such as learning. These emotions may be modified via emotion regulation (ER). The dominant process model of ER (PMER) proposed by J. Gross, however, provides a domain-general account of ER strategies and has not had substantial contact with theories of achievement emotions such as R. Pekrun's control-value theory (CVT) and the academic achievement literature. Moreover, ER has not been a focal point of major theories related to achievement emotions, such as CVT. We propose an integrated model of ER in achievement situations (ERAS) that integrates propositions about the generation of emotions from CVT with propositions about how emotions are regulated and types of ER strategies from PMER. The ERAS model also offers new propositions regarding how different achievement situations, object foci, and time frames, as well as discrete emotions with different appraisal patterns, impact ER strategies.